Phosphate limitation induces the intergeneric inhibition of Pseudomonas aeruginosa by Serratia marcescens isolated from paper machines. Issue 3 (11th March 2013) - Kuo, Pei‐An; Kuo, Chih‐Horng; Lai, Yiu‐Kay; Graumann, Peter L.; Tu, Jenn
Abstract Phosphate is an essential nutrient for heterotrophic bacteria, affecting bacterioplankton in aquatic ecosystems and bacteria in biofilms. However, the influence of phosphate limitation on bacterial competition and biofilm development in multispecies populations has received limited attention in existing studies. To address this issue, we isolated 13 adhesive bacteria from paper machine aggregates. Intergeneric inhibition of Pseudomonas aeruginosa WW5 by Serratia marcescens WW4 was identified under phosphate‐limited conditions, but not in Luria–Bertani medium or M9 minimal medium. The viable numbers of the pure S. marcescens WW4 culture decreased over 3 days in the phosphate‐limited medium; however, the mortality of S. marcescens WW4 was significantly reduced when it was co‐cultured with P. aeruginosa WW5, which appeared to sustain the S. marcescens WW4 biofilm. In contrast, viable P. aeruginosa WW5 cells immediately declined in the phosphate‐limited co‐culture. To identify the genetic/inhibitory element(s) involved in this process, we inserted a mini‐Tn5 mutant of S. marcescens WW4 that lacked inhibitory effect. The results showed that an endonuclease bacteriocin was involved in this intergeneric inhibition by S. marcescens WW4 under phosphate limitation. In conclusion, this study highlights the importance of nutrient limitation in bacterial interactions and provides a strong candidate gene for future functional characterisation.